Alcohol and its uses under Islamic scope (Khairulummah, 2022)
Alcohol derived from honey, wheat, barley or corn is haram when used as an intoxicant, in an amount that intoxicates. But, if not used in any such manner, and intended to use for medical purpose, hygiene, perfume, etc., then it would be permissible. There are some faqīhs, particularly of the Hanafi school, who take the concept of khamr literally and forbid only grape-based (or date-based) alcoholic beverages, allowing those made with other fruits, grains, or honey. This is, however, a minority opinion.Alcohol in Islam, Basically the world's religions have had differing relationships with alcohol. Many religions forbid alcoholic consumption or see it as sinful or negative. Others have allocated a specific place for it, such as in the Christian practice of using wine during the Eucharist rite. But according to Islam there is a consensus among theologians that the word khamr, meaning "intoxicants", refers to alcohol and all similar kind of beverages causing drunkenness, and that alcohol consumption is prohibited by Islam because it weakens the conscience of the believer. But on the other hand modern world is using alcohol as a preserver in different ways, so this article may highlight the correct ways of using of alcohol according to Islamic teachings.
Keywords: Quran, Hadith, Jurist, Alcohol, Quantity, Quality, Verse.